(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To survey AMH levels and determine the response point to ovarian stimulation therapy of AMH levels in infertile and subfertile patients. Subjects and methods: A cross-sectional study was conducted on 278 female patients of reproductive age (18-45 years old), diagnosed with infertility (primary or secondary) and treated with ovarian stimulation at the Department of Reproductive Support, Thai Nguyen A Hospital. Results: The average AMH concentration in the study was 3.93 ± 2.89 (ng/mL), the median value was 3.0 ng/mL, the maximum value was 16.7ng/ml and the minimum was 0.243ng/mL. The average AMH concentration and the number of reserve oocytes are inversely proportional to the patient’s age, especially after the age of 35, it is only half of that of the age of 19-24. The AMH concentration is moderately positively correlated with the number of oocytes obtained after ovarian stimulation. When the AMH concentration is ≤ 1.1 ng/mL, it shows that the patient responds poorly or almost does not respond to ovarian stimulation. With an AMH concentration = 1.2 ng/mL, the patient responds poorly to ovarian stimulation, an AMH concentration of 3.1-4.4 ng/mL, the patient responds well to ovarian stimulation, greater than 4.5 ng/mL is the threshold value for excessive response to ovarian stimulation. Conclusions: AMH concentration decreases with age and positively correlates with the number of oocytes obtained after ovarian stimulation. The threshold of AMH that responds well to ovarian stimulation is 4.5 ng/mL.